The shrinkage of justice and hospital facilities in small French cities (2000–2016). Issue 3 (3rd July 2021) - Baudet-Michel, Sophie; Chouraqui, Julie; Conti, Benoit; Guiraud, Noé; Le Neindre, Charlène; Toutin, Gilles
ABSTRACT: In many countries, the objective of reducing public spending combined with the introduction of New Public Management reforms have led to changes in the territorial organization of public services and to a withdrawal of public facilities in many places. Our hypothesis is that in France, this territorial process has not occurred in the same way in all cities. We assume that while medium-sized cities are seeing a reduction in some public service facilities, their disappearance usually occurs in small cities. Larger metropolitan areas have not been affected by such territorial retrenchment of public services facilities. These differences could lead to increased territorial inequalities at the level of urban systems and to a marginalization of some small cities. This paper examines these processes through a quantitative analysis of changes in the location of justice courts and hospital beds from 2000 to 2016, within French Functional Urban Areas. It shows that the decrease in the number of justice and hospital facilities was significant and has affected small cities.